Influence of Leader Member Exchange and Islamic Work Ethic on Employee Performance With Organizational Citizenship Behavior as Intervening Variable - Arini Tri Purwanti; Lilik Indayani (Indonesian Journal of Islamic Studies, 2022)
This study aims to determine the effect of Leader Member Exchange and Islamic work ethic on employee performance with organizational citizenship behavior as an intervening variable in Mbok Surip Bone Soft Chicken. This research is a type of quantitative research with hypothesis testing. The sample in this study was 100 employees on all employees of Mbok Surip Bone Soft Chicken. The analytical tool used in this research is path analysis technique with the help of SmartPLS software version 3.0 for windows. This study uses primary data and secondary data, primary data obtained from a questionnaire whose measurement uses a Likert scale which was tested for validity and reliability, while secondary data was obtained from company documents. The results of this study prove that (1) There is a positive and significant relationship between Leader Member Exchange and Employee Performance. (2) There is a positive and significant relationship between Islamic Work Ethic and Employee Performance (3) Leader Member Exchange has a positive and significant effect on Organizational Citizenship Behavior (4) Islamic Work Ethic has a positive and significant effect on Organizational Citizenship Behavior, (5) There is a positive and significant relationship between Employee Performance and Organizational Citizenship Behavior, (6) Leader Member Exchange has a positive and significant relationship on employee performance with organizational citizenship behavior as an intervening variable, (7) Organizational Citizenship Behavior cannot mediate Islamic Work Ethic and Employee Performance.